Analisis Kepemimpinan pada Dinas Sosial Kabupaten Maros dalam Peningkatan Kinerja Pegawai - Yelli Effrisa; Amy Yayuk Sri Rahayu (Syntax Corporation, 2023)
The purpose of this study was to determine the leadership of the Head of Social Services in increasing work motivation and performance of Social Service employees in Maros Regency. This study used an online survey (in the network) with a descriptive research type. This type was chosen in order to provide an overview and explanation of the relationship between the leadership of the Head of Social Services and the motivation of employee performance in Social Service agencies. All employees of the Maros District Social Service constitute the population in this study, while the sample is the Head of Social Services and the Secretary of Social Services. Purposive sampling is the sampling technique chosen in this study. Research shows that the Leadership Pattern used in the Head of Social Services in increasing employee motivation and performance in Social Services in Maros Regency can be seen from employee involvement in program planning, the level of communication between the Head of Social Services and employees is still classified as medium, the Head of Social Services often gives awards to employees, the level of punishment / punishment to employees is classified as low, and the level of supervision of employee activities is classified as moderate